2021
DOI: 10.3390/cancers13061350
|View full text |Cite
|
Sign up to set email alerts
|

A Drastic Shift in Lipid Adducts in Colon Cancer Detected by MALDI-IMS Exposes Alterations in Specific K+ Channels

Abstract: Even though colorectal cancer (CRC) is one of the most preventable cancers, it is one of the deadliest, and recent data show that the incidence in people <50 years has unexpectedly increased. While new techniques for CRC molecular classification are emerging, no molecular feature is as yet firmly associated with prognosis. Imaging mass spectrometry (IMS) lipidomic analyses have demonstrated the specificity of the lipid fingerprint in differentiating pathological from healthy tissues. During IMS lipidomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Even more far-reaching than single molecule MPMs, data-integrating probability maps of entire lipid classes in SwissLipids (https://www.swisslipids.org) 15 , of large groups of molecules such as potassium adducts of lipids 10,16 or of any other user-defined set of metabolites, so called collective-projection probability maps (CPPM), pave the way for visualization and exploration of integrated MSI data: Here, molecular ensembles are transformed to their respective SPP representations, then collectively projected into a single image space (Fig. 2A), and finally subjected to spatial probabilistic mapping into CPPMs (Fig.…”
Section: Fig 1b)mentioning
confidence: 99%
See 1 more Smart Citation
“…Even more far-reaching than single molecule MPMs, data-integrating probability maps of entire lipid classes in SwissLipids (https://www.swisslipids.org) 15 , of large groups of molecules such as potassium adducts of lipids 10,16 or of any other user-defined set of metabolites, so called collective-projection probability maps (CPPM), pave the way for visualization and exploration of integrated MSI data: Here, molecular ensembles are transformed to their respective SPP representations, then collectively projected into a single image space (Fig. 2A), and finally subjected to spatial probabilistic mapping into CPPMs (Fig.…”
Section: Fig 1b)mentioning
confidence: 99%
“…They generally enable new types of arithmetic operations with data, e.g., analysis of localized events and advanced statistical and homogeneity analysis of spatial data 8 . To this end, moleculaR provides the scientific community with solutions for molecular spatial probability mapping and for collective visualization and analysis of molecular ensembles, e.g., alkali metal adducts as ion milieu indicators 10 , energy charge as correlate of metabolic hotspots or entire lipid classes as the basis for the analysis of metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It also encodes an aldo-keto reductase and negatively regulates members of the voltage-gated potassium channel family [ 20 ]. Some studies have found that KCNAB2 may be involved in the occurrence and development of lymphoma [ 21 ], colorectal cancer [ 22 ], pituitary tumor [ 23 ], and neuroblastoma [ 24 ], but its role in lung adenocarcinoma remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the circulating lipids represent dietary nutrient intake and impacts, regulate hormonal and immunological responses and convey interorgan communications in cancer [4,5]. With the development of high throughput lipidomics and mass-spectrometry-based lipid imaging, an exponentially increased number of cancer-related lipid changes have been identified in cancer cells, animal models and clinical cohorts [6][7][8][9]. These often uncover previously overlooked lipid species in cancer, which offer new avenues for cancer diagnosis and treatment [6,8].…”
Section: Introductionmentioning
confidence: 99%